Palestinian Bereaved Mothers of Martyrs: Religious and National Discourses of Sacrifice and Bereavement - Hamamra, Bilal (Women & criminal justice, 2023)
This article, which employs interviews as its central methodology, examines Palestinian mothers’ reproduction of, opposition to, the Palestinian culture of martyrdom. Palestinian nationalist discourses encourage mothers to produce fighters and to re-produce the religious and national discourses on martyrdom by receiving their sons’ acts of martyrdom with celebration which signifies their adherence to the hegemonic masculine model of bereavement based on emotional restraint and expressing the necessity of martyrdom. Based on this logic, religious and national discourses function as a defensive mechanism that helps mothers to cope with their loss. However, some mothers prefer the well-being of their families over the abstract ideals of heroism and sacrifice, opposing the religious and national discourses that shape the Palestinian collective identity. While the mothers who perpetuate the culture of sacrifice are promoted socially, politically and symbolically, those who express their grief and condemnation of this culture are deemed traitorous and un-Islamic.